A Novel Speckle Noise Removal Algorithm Based on ADMM and Energy Minimization Method - Bo Chen; Yan Lv; Jinbin Zou; Wensheng Chen; Binbin Pan (Journal of Function Spaces)
Speckle noise removal in medical ultrasound images is a challenging task. In this paper, a new model is proposed to removal speckle noise, alternating direction method of multipliers algorithm is employed to solve the new energy minimization model. The convexity, existence, and uniqueness of the new energy minimization model’s solution are proved. Series of experiments are designed in this paper. Numerical results show that the new algorithm can reduce the step effect effectively obtain good results in visual effect and quantitative measures by comparing with some traditional models.